Assessment of the concentration, mobility, and bioavailability of Co, Cr, and Ni in soils from west Sabzevar ophiolitic complex, Iran - Maleknia, Parisa; Mazhari, Seyed Ali; Ugwonoh, Nelson; Czigány, Szabolcs; Kasina, Monika; Myovela, Justine L. (Journal of Asian Earth Sciences: X, 2025)
[Display omitted] •Total Ni, Cr exceed Iranian maximum permissible levels.•Agricultural soils show 2–3 × higher metal bioavailability than natural soils.•Bioavailable Ni and Cr exceed safe limits despite low mobility in total.•Lithology and land use are key factors in heavy metal distribution in soils. Soil contamination by heavy metals poses significant risks to ecosystems and human health, necessitating assessments beyond total concentrations to evaluate bioavailability and mobility. This study investigates heavy metal distribution in soils derived from ultramafic-rich ophiolitic complexes in the Sabzevar Range, northeastern Iran, focusing on Nickel (Ni), Chromium (Cr), and Cobalt (Co). Surface soils from Davarzan (sections A and B) and Namen areas were analyzed using total digestion, The diethylenetriaminepentaacetic acid (DTPA) single-step extraction, and The European Community Bureau of Reference (BCR) sequential extraction protocol to assess total concentrations, bioavailability, mobility and geochemical partitioning of heavy metals. Results indicate elevated total Ni and Cr concentrations exceeding Iranian maximum permissible concentrations (MPCs), with Ni and Cr classified as “heavily polluted” via geoaccumulation indices (Igeo ≥ 3). DTPA extraction revealed higher bioavailability in agricultural soils, emphasizing anthropogenic influences. BCR sequential extraction demonstrated that > 70 % of Co, >80 % of Cr, and > 75 % of Ni were sequestered in residual fractions, suggesting limited inherent mobility. However, absolute bioavailable and mobile fractions exceeded MPC thresholds in several samples, highlighting latent ecological risks. Spatial variability in metal behavior correlated with lithological provenance: ultramafic-derived soils (Davarzan Section A) exhibited maximal metal enrichment and mobility, while alluvial soils (Namen) showed dilution effects. Agricultural practices increased organic carbon and phosphate content, enhancing metal retention and mobilization. This study underscores the critical role of speciation analysis in environmental risk assessments in ultramafic terrains. Integrating bioavailability metrics with total concentrations provides a robust framework for prioritizing remediation strategies in contaminated ecosystems.